Komunikator - Universitas Muhammadiyah Yogyakarta. Program Studi Ilmu Komunikasi
Communication and mass media in Indonesia.
Keywords: Communication : Indonesia : Periodicals; Mass media : Indonesia : Periodicals; Communication; Mass media; Indonesia